Destructive black birds from the West – notes on an unusual vernacular 17th-century lament over the fall of Constantinople - Bzinkowski, Michał (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The vernacular lament known as Thrinos Konstantinoupoleos (Threnody on Constantinople) comes from the Codex Barberini Graecus 15, which is dated to the 17th century. It was written in the form of a letter by an unknown author to a recipient who also remains unknown. The author of the work imitates, albeit sometimes freely, the composition Peri arpagis kai adikias. Kai thrinos kai klauthmos peri tis Konstantinoupoleos by Matthew of Myra, a work that can be dated to before 1618. Surprisingly, the Thrinos Konstantinoupoleos has little in common with the lamentations over the fall of cities to which the threnodies for the fall of Constantinople belong. Its content is primarily a criticism of the Byzantines and an attempt to see the capture of the City as an inevitable event brought about by the Romaioi themselves. The composition bears no relation to the typical features of an elegy or an elogium. In this article, I focus on the features of this composition that distinguish it in character from other lamentations. Furthermore, by comparing relevant passages from the original text by Matthew of Myra, I attempt to show the profound originality of the author of Thrinos’ vision.